2022
DOI: 10.1002/bse.3111
|View full text |Cite
|
Sign up to set email alerts
|

How bricolage influences green management in high‐polluting manufacturing firms: The role of stakeholder engagement

Abstract: As green management (GM) matters not only for firms' competitiveness but also has social and health benefits, both the public and government often expect firms to apply it. However, the current literature fails to provide a detailed explanation of how emerging market firms in high‐polluting manufacturing (HPM) industries deal with challenges when applying GM activities, even though these firms may be a key source of environmental problems. To address this research gap, we draw upon a subjectivist view of resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 115 publications
0
16
0
Order By: Relevance
“…This reconciles the existing debate about SCM effects on GM (Ahmed et al, 2020;Kobarg et al, 2020;Wu et al, 2020). This is done by verifying that supplier-firm cooperation can enhance a manufacturing firm's GM by providing complementarity engineering and manufacturing technologies (Wu & Liu, 2022), supplying green raw materials and components (Andersén, 2021), and providing necessary knowledge and information for GM (Zhao et al, 2018).…”
Section: Theoretical Contributionsmentioning
confidence: 60%
See 3 more Smart Citations
“…This reconciles the existing debate about SCM effects on GM (Ahmed et al, 2020;Kobarg et al, 2020;Wu et al, 2020). This is done by verifying that supplier-firm cooperation can enhance a manufacturing firm's GM by providing complementarity engineering and manufacturing technologies (Wu & Liu, 2022), supplying green raw materials and components (Andersén, 2021), and providing necessary knowledge and information for GM (Zhao et al, 2018).…”
Section: Theoretical Contributionsmentioning
confidence: 60%
“…and derived from the literature (e.g., Chandler et al, 2011;Jaworski & Kohli, 1993;Li et al, 2011;Qian et al, 2013;Shu et al, 2016). We incorporated five control variables-firm age, size, stage, R&D intensity, and technological uncertainty-according to existing relevant studies that provide alternative explanations for GM performance (e.g., Shu et al, 2016;Wu & Liu, 2022;Zhou et al, 2019). The measurements of firm age, size, stage, and R&D intensity are shown in Table 4.…”
Section: Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bricolage initiates new product development pathways by using everything you have at home to discover the surroundings and related opportunities (Suire, 2019). In their study, Wu & Liu (2022) showed that organizations could use bricolage to innovate green products positively, but the effects depend on the participation of various stakeholders. The quality of a product can be improved by an adequate understanding of the product and practical testing of the product concept, which gives a clear picture of the product and provides insights into the product development.…”
Section: Bricolage and New Product Developmentmentioning
confidence: 99%